Gradient design of Pt/C ratio and Nafion content in cathode catalyst layer of PEMFCs. (14th December 2017) - Chen, Guang-Ying; Wang, Cheng; Lei, Yi-Jie; Zhang, Jianbo; Mao, Zhiming; Mao, Zong-Qiang; Guo, Jian-Wei; Li, Jianqiu; Ouyang, Minggao
Abstract: In order to increase the utilization of Pt, reduce mass transfer loss and improve the performance of polymer electrolyte membrane fuel cells (PEMFCs) under low humidity and high current densities, the cathode catalyst layers with two layers of different Pt/C ratio and Nafion content are fabricated and evaluated. Polarization curves (IVs), cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) are employed to characterize and compare the effects of Pt/C ratio and Nafion content gradient on the performance of PEMFCs under different humidification conditions. The results indicate that the performance of the membrane electrode assembly (MEA) can be significantly improved via allocating more Nafion and Pt/C in the sublayer near the membrane in cathode catalyst layer. The MEA with optimal gradient cathode catalyst layer results in improved catalysts utilization compared to MEA with single cathode catalyst layer, 0.403 g kWrated −1 and 0.711 g kWrated −1 under 80 RH% and 20 RH%, respectively. The areal power density of the optimal MEA is 28.4% and 135.7% higher than the conventional single-layer catalyst layer MEA under high and low humidity, respectively. Highlights: Gradient design is implemented through double layer construction of cathode catalyst layer. Three Pt/C ratio gradients: 60-60, 40–70, 70–40, (wt%, inner – outer layer), are evaluated. Three Nafion ionomer content gradients (wt%): 24.5–24.5, 33–23, 40–20, are examined. The optimal design is 70–40 for Pt/C ratio gradient, and 33–23 for Nafion content gradient. The gradient design is found to be particularly effective at low humidity conditions.